Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.18632/oncotarget.19331
|View full text |Cite
|
Sign up to set email alerts
|

OncomiR-17-5p: alarm signal in cancer?

Abstract: Soon after microRNAs entered the stage as novel regulators of gene expression, they were found to regulate -and to be regulated by- the development, progression and aggressiveness of virtually all human types of cancer. Therefore, miRNAs in general harbor a huge potential as diagnostic and prognostic markers as well as potential therapeutic targets in cancer.The miR-17-92 cluster was found to be overexpressed in many human cancers and to promote unrestrained cell growth, and has therefore been termed onco-miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 124 publications
2
35
0
Order By: Relevance
“…Previous studies have shown that microRNAs participate in lung cancer development and progression, and may be potential prognostic biomarkers for lung cancer (19,20). In this study, miR-1323 was selected through an online database, and was found to predict the survival of lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that microRNAs participate in lung cancer development and progression, and may be potential prognostic biomarkers for lung cancer (19,20). In this study, miR-1323 was selected through an online database, and was found to predict the survival of lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…5 for interaction details. Both has-miR-20b and has-miR-17 are OncomiRs [ 52 ], acting on LIMA1 tumor suppressor gene [ 53 ]. Their interaction leads to LIMA1 degradation, thus decreasing its expression in breast cancer tissue ( p -value <0.05).…”
Section: Resultsmentioning
confidence: 99%
“…(PDCD4, PTEN, P21, STAT3) and miR-20a-5p (P21) (Bobbili, Mader, Grillari, & Dellago, 2017;Fang, Wang et al, 2017) regulated the procession of embryo implantation (Andreas et al, 2016, Li, Devi, Bao, Mao, & Gibori, 2008Sun, Bartos, Whitsett, & Dey, 2013;Y. Zhang, Ni, et al, 2018), indicating that miR-17-92 clusters may closely relate to embryo implantation.…”
Section: Discussionmentioning
confidence: 99%